Odpowiedzi

2010-03-10T08:29:15+01:00
B)
4x-2y =6 /*3
3x+6y=12

12x-6y=18
3x+6y=12
---------------
15x=30
x=2

3x+6y=12
x=2

6+6y=12
x=2

a)
2x-3y=-5
-x+5y=6 /*2

2x-3y=-5
-2x+10y=12
-------------
7y=7 /:7
y=1

2x-3y=-5
y=1

2x-3*1=-5
y=1

2x-3=-5
y=1

2x=-5+3
y=1

2x=-2 /:2
y=1

x=-1
y=1



2010-03-10T08:33:08+01:00
A)
{ 2x-3y=-5
{ -x+5y=6 /*2

{ 2x-3y=-5
+ {-2x+10y=12
----------------------------
7y=7/:7
y=1


2x-3y=-5
2x-3=-5
2x=-5+3
2x=-2/:2
x=-1

{y=1
{x=-1




b)
{ 4x-2y=6/*(-3)
{ 3x+6y=12/*4

{-12x+6y=-18
+{12x+24y=48
--------------------------
30y=66/:30
t=2,2

4x-2y=6
4x-4,4=6
4x=6+4,4
4x=10,4/:4
x=2,6

{y=2,2
{x=2,6



c)
{ 2x+2y=5(x-3)
{ 4(x+5)-2(y-3)=34

{2x+2y=5x-15
{4x+20-2y+6=34

{2x+2y-5x=-15
{4x-2y=34-20-6

{-3x+2y=-15 /*4
{4x-2y=8 /*3

{-12x+8y=-60
+{12x-6y=24
------------------------
2y=-36/:2
y=-18


4x-2y=8
4x+36=8
4x=8-36
4x=-24/:4
x=-6

{y=-18
{x=-6

















2010-03-10T09:03:55+01:00
A)
{ 2x-3y=-5
{ -x+5y=6 /*2

2x-3y=-5
-2x+10y=12 Metoda przeciwnych znaków
----------------
7y=7 /:7
y=1

2x-3*1=-5
2x-3=-5
2x=-5+3
2x=-2 /:2
x=-1
y=1


b)
{ 4x-2y=6 /*3
{ 3x+6y=12

12x-6y=18
3x+6y=12
---------------
15x=30 /:15
x=2

4*2-2y=6
8-2y=6
8-6=2y
2=2y /:2
y=1
x=2

c)
{ 2x+2y=5(x-3)
{ 4(x+5)-2(y-3)=34

2x+2y=5x-15
4x+20-2y+6=34

2x-5x+2y=-15
4x-2y=34-20-6

-3x+2y=-15
4x-2y=8
------------
x=-7
4*-7-2y=8
-28-2y=8
-2y=8+28
-2y=36 /:-2
y=-18
x=-7